Zapisz w jak najprostszej postaci:
a) 2(x-y)(x+y)-3(x-2y)²
b) 5(s+3t)(3t-s)-2(s+2t)²
c) (z+0,3)²+(z+0,2)(0,2-z
d) (a-3)²-(a+4)(4-a)-6(3-a)
e) (5-2x)²+(x+√5)-5(x+2)²
f) (2k-l²)²-2(k+l²)(l²-k)+(k+2l²)²

dziekuje za pomoc :)
praca jest na jutro a wiec prosze o szybkie jego wykonanie xD

2

Odpowiedzi

2009-12-02T21:16:44+01:00
A) 2(x²-y²)-3(x²-4xy+4y²)=2x²-2y²-3x²+4xy-4y²= -x²-6y²+4xy
b)(5s+15t)(3t-s)-2(s²+4st+4t²)=15st-5s²+45t²-15st-2s²-8st-8t²=-7s²+37t²-8st
c)z²+0,6z+0,09+ 0,2z -z²+0,04 -0,2z = 0,6z +1,3
d)a²-6a+9- 4a +a² -16 +4a -18+6a = 2a²-25
e)25 -20x +4x² +x+√5 -5x²- 20x - 20 = -x² -39x + √5
f)4k²-4kl² + l⁴ +2k² -2kl² -2l⁴ +2kl²+ k²+4kl²+4l⁴= 3l⁴+2kl²+7k²
1 5 1
  • eaak
  • Rozwiązujący
2009-12-02T21:30:29+01:00
2(x-y)(x+y)-3(x-2y)²=2(x²-y²)-3(x²-2xy+2y²)=2x²-2y²-3x²+6xy+4y²=-x²+2y²+6xy